Recessive SLC19A2 mutations are a cause of neonatal diabetes mellitus in thiamine-responsive megaloblastic anaemia - Shaw‐Smith, Charles; Grulich-Henn, Jürgen (Pediatric diabetes, 2012)
Permanent neonatal diabetes mellitus (PNDM) is diagnosed within the first 6 months of life, and is usually monogenic in origin. Heterozygous mutations in ABCC8, KCNJ11, and INS genes account for around half of cases of PNDM; mutations in 10 further genes account for a further 10%, and the remaining 40% of cases are currently without a molecular genetic diagnosis. Thiamine-responsive megaloblastic anaemia (TRMA), due to mutations in the thiamine transporter SLC19A2, is associated with the classical clinical triad of diabetes, deafness, and megaloblastic anaemia. Diabetes in this condition is well described in infancy but has only very rarely been reported in association with neonatal diabetes. We used a combination of homozygosity mapping and evaluation of clinical information to identify cases of TRMA from our cohort of patients with PNDM. Homozygous mutations in SLC19A2 were identified in three cases in which diabetes presented in the first 6 months of life, and a further two cases in which diabetes presented between 6 and 12 months of age. We noted the presence of a significant neurological disorder in four of the five cases in our series, prompting us to examine the incidence of these and other non-classical clinical features in TRMA. From 30 cases reported in the literature, we found significant neurological deficit (stroke, focal, or generalized epilepsy) in 27%, visual system disturbance in 43%, and cardiac abnormalities in 27% of cases. TRMA should be considered in the differential diagnosis of diabetes presenting in the neonatal period.